Conservation of the OmpC Porin Among Typhoidal and Non-Typhoidal Salmonella Serovars - Valero-Pacheco, Nuriban; Blight, Joshua; Aldapa-Vega, Gustavo; Kemlo, Phillip; Pérez-Toledo, Marisol; Wong-Baeza, Isabel; Kurioka, Ayako; Perez-Shibayama, Christian; Gil-Cruz, Cristina; Sánchez-Torres, Luvia E.; Pastelin-Palacios, Rodolfo; Isibasi, Armando; et al. (Frontiers in Immunology, 2020)
Salmonella enterica infections remain a challenging health issue, causing significant morbidity and mortality worldwide. Current vaccines against typhoid fever display moderate efficacy whilst no licensed vaccines are available for paratyphoid fever or invasive non-typhoidal salmonellosis. Therefore, there is an urgent need to develop high efficacy broad-spectrum vaccines that can protect against typhoidal and non-typhoidal Salmonella. The Salmonella outer membrane porins OmpC and OmpF, have been shown to be highly immunogenic antigens, efficiently eliciting protective antibody, and cellular immunity. Furthermore, enterobacterial porins, particularly the OmpC, have a high degree of homology in terms of sequence and structure, thus making them a suitable vaccine candidate. However, the degree of the amino acid conservation of OmpC among typhoidal and non-typhoidal Salmonella serovars is currently unknown. Here we used a bioinformatical analysis to classify the typhoidal and non-typhoidal Salmonella OmpC amino acid sequences into different clades independently of their serological classification. Further, our analysis determined that the porin OmpC contains various amino acid sequences that are highly conserved among both typhoidal and non-typhoidal Salmonella serovars. Critically, some of these highly conserved sequences were located in the transmembrane β-sheet within the porin β-barrel and have immunogenic potential for binding to MHC-II molecules, making them suitable candidates for a broad-spectrum Salmonella vaccine. Collectively, these findings suggest that these highly conserved sequences may be used for the rational design of an effective broad-spectrum vaccine against Salmonella.